2016
DOI: 10.4103/0973-1296.182154
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin suppresses the migration and invasion in human colon cancer Caco-2 cells through regulating toll-like receptor 4/Nuclear Factor-kappa B pathway

Abstract: Objective:The migration and invasion features, which were associated with inflammatory response, acted as vital roles in the development of colon cancer. Quercetin, a bioflavonoid compound, was widely spread in vegetables and fruits. Although quercetin exerts antioxidant and anticancer activities, the molecular signaling pathways in human colon cancer cells remain unclear. Hence, the present study was conducted to investigate the suppression of quercetin on migratory and invasive activity of colon cancer and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 52 publications
0
31
0
Order By: Relevance
“…[4546] Both in vitro and in vivo cancer studies, quercetin was said to have a beneficial effect against prostate cancer. [47]…”
Section: Introductionmentioning
confidence: 99%
“…[4546] Both in vitro and in vivo cancer studies, quercetin was said to have a beneficial effect against prostate cancer. [47]…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin (3,3′,4′,5,7-pentahydroxyflavone; molecular weight, 302 g/mol), a bioactive flavonoid is widely present in various fruits and vegetables, including onions, and the most studied quercetin primary sources are broccoli, apples, berry crops and grapes, and is also in certain herbs, tea and wine ( 6 , 7 ). Emerging evidence demonstrated that quercetin has potential benefits for treatment of cancer and endometriosis with no obvious adverse actions, with anti-carcinogenic, anti-inflammatory, anti-viral, anti-oxidant, and psychostimulant activities, as well as the ability to inhibit lipid peroxidation, platelet aggregation and capillary permeability, and to stimulate mitochondrial biogenesis ( 8 , 9 ). However, the underlying mechanism of quercetin alleviating generalized hyperalgesia of adenomyosis remains poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, our lab has demonstrated the ability of quercetin to reduce the numbers of high multiplicity aberrant crypt foci (HMACF), which are thought to be most indicative of eventual tumor formation [203, 204]. A reduction in proliferation and an increase in apoptosis were also observed in rats fed quercetin, and these effects are thought to be related to observed reductions in pro-inflammatory mediators, cyclooxygenase 1 and 2 (COX-1 and COX-2) [204], as well as through impacts on other signaling pathways including NF-κB, PI3K/Akt/mTOR, and JNK/JUN [204207]. Quercetin has also been shown to reduce the incidence, multiplicity, and size of colorectal tumors in male F344 rats treated with AOM, compared to control diet animals [208].…”
Section: Dietary Mediators Of Colon Tumorigenesismentioning
confidence: 99%